Rehabilitation and Reintegration Programming adjunct to Female Genital Fistula Surgery: A systematic scoping review - El Ayadi, Alison M.; Obore, Susan; Byamugisha, Josaphat; Barageine, Justus K. (International Journal of Gynecology & Obstetrics, 2020)
Female genital fistula is associated with significant physical, psychological, and economic consequences; however, a knowledge and practice gap exists around services adjunct to fistula surgery. To examine rehabilitation and reintegration services provided adjunct to genital fistula surgery, map existing programming and outcomes, and identify areas for additional research. We searched the published and grey literature from January 2000 to June 2019. Two reviewers screened articles and extracted data using standardized methods. Research and programmatic articles describing service provision in addition to female genital fistula surgery were included. Of 3047 published articles and 2623 unpublished documents identified, 26 and 55, respectively, were analyzed. Programming identified included combinations of health education, physical therapy, social support, psychosocial counseling, and economic empowerment, largely in sub-Saharan Africa. Improvements were noted in physical and psychosocial health. Existing literature supports holistic fistula care through adjunct reintegration programming. Improving the evidence base requires implementing robust study designs, increasing reporting detail, and standardizing outcomes across studies. Increased financing for holistic fistula care is critical for developing and supporting programming to ensure positive outcomes.